Central role of the spleen in malaria parasite clearance. - Chotivanich, K; Udomsangpetch, R; Mcgready, R; Proux, S; Newton, P; Pukrittayakamee, S; Looareesuwan, S; White, N (2002)
In acute malaria, red blood cells (RBCs) that have been parasitized, but no longer contain a malaria parasite, are found in the circulation (ring-infected erythrocyte surface antigen [RESA]-RBCs). These are thought to arise by splenic removal of dead or damaged intraerythrocytic parasites and return of the intact RBCs to the circulation. In a study of 5 patients with acute falciparum malaria who had previously undergone splenectomy, it was found that none of these 5 patients had any circulating RESA-RBCs, in contrast to the uniform finding of RESA-RBCs in all patients with acute malaria and intact spleens. Parasite clearance after artesunate treatment was markedly prolonged, although the parasites appeared to be dead and could not be cultured ex vivo. These observations confirm the central role of the spleen in the clearance of parasitized RBCs after antimalarial treatment with an artemisinin derivative. Current criteria for high-grade antimalarial drug resistance that are based on changes in parasitemia are not appropriate for asplenic patients.